U.S. – E.U. Economic Relations in the Context of Economic Globalization - Gabriel-Andrei Donici; Andreea Maha (CES Working Papers, 2010)
Traditionally, U.S. and E.U. are the major economic forces in the world. Today, in the context of economic globalization, relations between the U.S. and E.U. continue to guide the world. Yet the economic crisis and the rise of third world countries are affecting their global share.
Keywords: 330; globalization; world power; trade flows; multinationals; investment funds